How safety leadership, social capital, and safety awareness affect safety citizenship behavior: a mediation perspective - Andjar Budi Wibawanti; Lim Sanny; Denny Siahaan; Sundring Pantja Djati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Safety citizenship behavior (SCB) of the ship crew is essential to maritime safety. Therefore, using safety motivation as a mediating mechanism, this research attempts to understand and quantify the impact of safety leadership, social capital, and safety awareness on ship crew SCB. The study employs a causal design and survey methods in a quantitative manner. 120 crew members of passenger ships that were docked at Tanjung Priok Port in Jakarta made up the sample. A Likert scale questionnaire was utilized as the research tool for safety leadership, social capital, safety awareness, safety motivation, and SCB. Google Forms-formatted questionnaires were sent out by email and WhatsApp. Partial least squares (PLS)-based structural equation modeling (SEM) analysis was used to analyze the data. The study's findings indicate that safety leadership, social capital, safety awareness, and safety motivation all have a significant impact on SCB; additionally, safety leadership, social capital, and safety awareness all have a significant impact on safety motivation, which in turn has a significant impact on SCB through safety motivation. These results validate the novelty of the safety leadership, social capital, and safety awareness mediation model's effect on the SCB of passenger ship crew through safety motivation.